2018
DOI: 10.1055/s-0038-1625983
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thrombosis in Antithrombin Deficiency: A Systematic Review and Bayesian Meta-analysis

Abstract: Antithrombin deficiency is a strong risk factor for venous thromboembolism (VTE), but the absolute risk of the first and recurrent VTE is unclear. The objective of this paper is to establish the absolute risks of the first and recurrent VTE and mortality in individuals with antithrombin deficiency. The databases Embase, Medline Ovid, Web of Science, the Cochrane Library, and Google Scholar were systematically searched for case-control and cohort studies. Bayesian random-effects meta-analysis was used to calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…Antithrombin deficiency is a rare variant that is associated with greatly increased risk of incident VTE (OR, 14.0 [95% CI, 5.5–29.0]). 48 A bayesian meta-analysis found that for childbearing females with this variant, VTE risk was 7% in the antepartum period and 11% postpartum. 49…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…Antithrombin deficiency is a rare variant that is associated with greatly increased risk of incident VTE (OR, 14.0 [95% CI, 5.5–29.0]). 48 A bayesian meta-analysis found that for childbearing females with this variant, VTE risk was 7% in the antepartum period and 11% postpartum. 49…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…One special case which deserves consideration is the presence of antithrombin deficiency, which is a potent inherited risk factor for VTE (OR: 14.0; 95% CI 5.5 to 29.0) and increases the absolute risk of a first VTE to >1% per year [65]. The risk of recurrent VTE for these patients is substantial, and antithrombin deficient patients should be continued on long-term anticoagulation after a first episode of VTE.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…For example, Esmon et al 20 found that the increase in CRP resulted in a decrease in AT, while the decrease in AT reduced anticoagulant activity, one of the reasons for the hypercoagulable state leading to DVT. 21 In immune diseases, inflammatory stimulants such as CRP and tumor necrosis factor can promote clotting, leading to elevated clotting factor levels and DVT formation. 22 , 23 In general, multiple factors and mechanisms combine in the development of PTE in ITP patients.…”
Section: Discussionmentioning
confidence: 99%